The Effect Of Interactive Multimedia-Assisted Learning Model On Students' Practice Learning At SMAN 7 Bengkulu Selatan - Nevia Putri Wangi; Yenni Fitria; Hermawansa Hermawansa (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of interactive multimedia-assisted drill learning on practical learning of students of SMAN 7 Bengkulu Selatan. The method used in this study is a quantitative approach with a quasi-experimental method. This study used subjects of class X students of SMAN 7 Bengkulu Selatan with a sample of 2 classes, namely class Xa totaling 33 students as the experimental class and class Xb totaling 33 students as the control class. The techniques used to collect data are Observation, Tests, Questionnaires, and Documentation. Based on the results of the research conducted, it can be seen from the discussion through the analysis method of obtaining Pretest and Posttest scores using interactive multimedia-assisted drill learning on students' practical learning which states that interactive multimedia-assisted drill learning on students' practical learning has a significant influence on student learning outcomes in informatics subjects at SMAN 7 Bengkulu Selatan. In testing the hypothesis using the Independent Sample t-test test, it shows an increase in learning outcomes with a significant value of 0.000 <0.05 so that the hypothesis can be accepted.